PERSEPSI PETANI TERHADAP KINERJA USAHA USAHA BAWANG MERAH PADA PROGRAM DAERAH DATARAN TINGGI DI KECAMATAN PUJON KABUPATEN MALANG - Mulyanto Pramono; Asnah; Eri Yusnita Arvianti (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
This study aims to analyze farmers' perceptions of the performance of red onion farming in the UPLAND program (The Development of Integrated Farming System in Upland Areas) in Pujon District, Malang Regency. The research was conducted from August to October 2024 using a quantitative approach through survey methods. The research sample consisted of 70 respondents selected using the simple random sampling technique from a population of 250 red onion farmers participating in the UPLAND program, spread across 7 farmer groups. The research variables consist of independent variables such as age (X₁), education (X₂), seedling needs (X₃), NPK fertilizer dosage (X₄), and production (X₅), a mediating variable of adoption level (Z), and a dependent variable of increased performance of red onion farming (Y). Data analysis uses Partial Least Square (PLS). The research results show that the variables of age, education, NPK fertilizer dosage, and production significantly affect the performance of red onion farming, while the seedling requirement variable does not have a significant effect. The adoption rate has proven to be a highly significant mediating variable in the relationship between all independent variables and farming performance. The UPLAND program successfully increased the total production of red onions by 15.56% from 112.10 tons to 129.54 tons and raised the total income of farmers by 9.53% from Rp 1,743,270,000 to Rp 1,909,425,000 despite a 1.24% decrease in the selling price of red onions.